Efek moderasi gender terhadap pengaruh literasi keuangan, faktor demografi, risk perception dan perilaku keuangan terhadap minat investasi mahasiswa (Studi kasus Universitas Alma Ata) - Hisyam, Muhammad; Nuansari, Shindy Dwita (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2023)
The objective of this study is to examine the moderating impact of gender on the relationship between investment interest among students and the influence of financial literacy, demographic factors, risk perception, and financial behavior. This is a quantitative study employing primary data, specifically information extracted directly from the responses of the participants. In this investigation, samples comprised ninety respondents. The methodology employed in this study is the multiple linear regression examination of the data. Demographic factors and financial behavior, in addition to financial literacy and risk perception, have a positive and statistically significant impact on the investment interest variable among students, according to the findings of this study. In contrast, the relationship between investment interest and the impacts of financial literacy, demographic factors, risk perception, and financial behavior remains unaffected by gender. Keywords: Financial Literacy, Demographic Factors, Risk Perception, Financial Behavior, Investment Interest, Gender